Manganese ferrite-graphite oxide-chitosan nanocomposite for efficient dye removal from aqueous and textile wastewater under UV and sunlight irradiation - Nazila Mohammad Hosseini; Shabnam Sheshmani; Ashraf S. Shahvelayati (Scientific Reports)
Abstract This study presents the development and characterization of manganese ferrite (MnFe2O4)-based nanocomposites with graphite oxide (GO) and chitosan (CS) for efficient dye removal from textile wastewater and aqueous solution. Comprehensive characterization was performed using FT-IR, Raman, XRD, BET, SEM, DRS and Zeta potential techniques. XRD analysis confirmed the cubic spinel structure of MnFe2O4, with characteristic peaks at 2θ = 32, 35, 48, 53, 62, and 64°. BET analysis revealed a high specific surface area of 442.57 m2/g and a pore diameter of 2.36 nm for the MnFe2O4/GO/CS nanocomposite. SEM imaging showed polyhedral MnFe2O4 particles (11–33 nm) deposited on a wrinkled graphite oxide matrix. DRS analysis indicated band gap energies of 3.1 eV for MnFe2O4, 3.0 eV for MnFe2O4/GO, and 3.5 eV for MnFe2O4/GO/CS. Zeta potential measurements showed a positive surface charge (+ 36.8 mV) for MnFe2O4/GO/CS. The MnFe2O4/GO/CS nanocomposite exhibited exceptional photocatalytic performance under UV light irradiation. It achieved 99.9 and 99.5% removal of Reactive Red 198 dye and Brilliant Blue FCF 133, respectively. The photocatalytic process followed pseudo-second-order kinetics (R2 = 0.99). In real textile wastewater treatment, the nanocomposite reduced BOD from 889 to 0.86 mg/L and COD from 1227 to 74 mg/L, with 96% dye removal. Also, MnFe2O4/GO/CS showed excellent performance under sunlight irradiation and maintained high removal efficiencies over multiple cycles, demonstrating good reusability. This study highlights the potential of the MnFe2O4-based nanocomposites as versatile and sustainable solutions for remediating dye-contaminated water.